EFFECTIVENESS OF DIGITAL-BASED ADMINISTRATIVE SERVICES THROUGH THE SIPRAJA APPLICATION IN DAMARSI VILLAGE, BUDURAN DISTRICT, SIDOARJO REGENCY - Amalia, Dinda Rizka; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the effectiveness of digital-based administrative services through the SIPRAJA (Sidoarjo Public Service System) application in Damarsi Village, Buduran District, Sidoarjo Regency. Method: This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The theory used refers to the effectiveness indicators from Sondang P. Siagian, namely resources, quantity and quality of services, time limits, and service procedures. Results: The results of the study based on indicators show: Resources, the availability of human resources is sufficient, but has not received formal training and the number of personnel is still limited. Number and Quality of Services, SIPRAJA is able to accelerate services, but the level of community utilization is still low due to minimal digital literacy. Service Time Limits. services can be carried out quickly, but their effectiveness depends on the readiness of operators and systems. Service Procedures, application procedures are systematic, but public understanding is still low due to lack of socialization. Novelty: The study provides an original descriptive analysis of digital-based administrative services in a village context using SIPRAJA, highlighting specific effectiveness challenges in human resources, service utilization, time limits, and procedural understanding.